Heidegger and Kabbalah : hidden gnosis and the path of poiesis - Wolfson, Elliot R. (New Jewish philosophy and thought., 2019)
While many scholars have noted Martin Heidegger's indebtedness to Christian mystical sources, as well as his affinity with Taoism and Buddhism, Elliot R. Wolfson expands connections between Heidegger's thought and kabbalistic material. By arguing that the Jewish esoteric tradition impacted Heidegger, Wolfson presents an alternative way of understanding the history of Western philosophy.